2014
DOI: 10.3989/gya.074113
|View full text |Cite
|
Sign up to set email alerts
|

Simultatenous determination of diacetyl and acetoin in traditional turkish butter stored in sheep’s rumen (Karinyagi)

Abstract: SUMMARY:Commercial Karinyagi (traditionally named karin) is made of cows' milk cream and is produced by filling butter in cleaned sheep's rumen. The effect of butter storage in sheep's rumen on the production of diacetyl and acetoin was investigated. These compounds were determined by GC-MS and they are the typical butter flavor commonly found in fermented dairy products. The modified method for the simultaneous extraction of diacetly and acetoin from butter samples was accurate and precise. The recoveries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Ergöz (2017) has also identified acetoin, 2-heptanone (milk flavor), and 2-nonanone (cooked milk flavor) in buffalo butter and has suggested that acetoin contributes to form the characteristic aroma of butter from buffalo cream. Gokce et al (2014) and Roosta et al (2014) have reported the presence of acetoin in butter samples. Çakmakçı and Hayaloğlu (2011) have stated that 2-pentanone, 2-heptanone, and 2-nonanone are the most abundant ketones in Ispir kaymak samples.…”
Section: Ketonesmentioning
confidence: 99%
“…Ergöz (2017) has also identified acetoin, 2-heptanone (milk flavor), and 2-nonanone (cooked milk flavor) in buffalo butter and has suggested that acetoin contributes to form the characteristic aroma of butter from buffalo cream. Gokce et al (2014) and Roosta et al (2014) have reported the presence of acetoin in butter samples. Çakmakçı and Hayaloğlu (2011) have stated that 2-pentanone, 2-heptanone, and 2-nonanone are the most abundant ketones in Ispir kaymak samples.…”
Section: Ketonesmentioning
confidence: 99%